Lignin‐Based Materials for Additive Manufacturing: Chemistry, Processing, Structures, Properties, and Applications. Issue 9 (19th January 2023) - Jiang, Bo; Jiao, Huan; Guo, Xinyu; Chen, Gegu; Guo, Jiaqi; Wu, Wenjuan; Jin, Yongcan; Cao, Guozhong; Liang, Zhiqiang
Abstract: The utilization of lignin, the most abundant aromatic biomass component, is at the forefront of sustainable engineering, energy, and environment research, where its abundance and low‐cost features enable widespread application. Constructing lignin into material parts with controlled and desired macro‐ and microstructures and properties via additive manufacturing has been recognized as a promising technology and paves the way to the practical application of lignin. Considering the rapid development and significant progress recently achieved in this field, a comprehensive and critical review and outlook on three‐dimensional (3D) printing of lignin is highly desirable. This article fulfils this demand with an overview on the structure of lignin and presents the state‐of‐the‐art of 3D printing of pristine lignin and lignin‐based composites, and highlights the key challenges. It is attempted to deliver better fundamental understanding of the impacts of morphology, microstructure, physical, chemical, and biological modifications, and composition/hybrids on the rheological behavior of lignin/polymer blends, as well as, on the mechanical, physical, and chemical performance of the 3D printed lignin‐based materials. The main points toward future developments involve hybrid manufacturing, in situ polymerization, and surface tension or energy driven molecular segregation are also elaborated and discussed to promote the high‐value utilization of lignin. Abstract : This article provides a comprehensive view of 3D printing techniques for lignin, and presents the state‐of‐the‐art of 3D printing of pristine lignin and lignin‐based composites. Importantly, the relationship between the lignin structures and the rheological behavior of lignin/polymer blends or composites, as well as, the resulted printability in combination with the potential problems and challenges are summarized.